2017
DOI: 10.1371/journal.pone.0187239
|View full text |Cite
|
Sign up to set email alerts
|

Raw pet food as a risk factor for shedding of extended-spectrum beta-lactamase-producing Enterobacteriaceae in household cats

Abstract: BackgroundClose contact between pets and owners provides the opportunity for transmission of antimicrobial resistant organisms like extended-spectrum beta-lactamase (ESBL)/AmpC beta-lactamase (AmpC)-producing Enterobacteriaceae, posing a risk to public health.ObjectivesTo investigate whether raw feed is a risk factor for household cats to shed ESBL-producing Enterobacteriaceae, a cohort study was designed. Additionally, raw and non-raw commercial pet food products were screened for the presence of ESBL-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 32 publications
4
51
0
1
Order By: Relevance
“…A study in the Netherlands reported that 28 of 35 raw pet food products yielded ESBL-positive E. coli (van Bree et al 2018), while in Italy, ESBL producers were prevalent among Salmonella isolates from date-expired human products available for pet food use (Bacci et al 2019). A second Dutch study also found that a similar proportion of raw products (14 of 18) yielded ESBL-or AmpC-positive Enterobacteriaceae compared with none of 35 processed products (Baede et al 2017), whilst 23% of Nordic raw food samples containing poultry meat yielded plasmid-borne AmpC genes (Nilsson 2015).…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…A study in the Netherlands reported that 28 of 35 raw pet food products yielded ESBL-positive E. coli (van Bree et al 2018), while in Italy, ESBL producers were prevalent among Salmonella isolates from date-expired human products available for pet food use (Bacci et al 2019). A second Dutch study also found that a similar proportion of raw products (14 of 18) yielded ESBL-or AmpC-positive Enterobacteriaceae compared with none of 35 processed products (Baede et al 2017), whilst 23% of Nordic raw food samples containing poultry meat yielded plasmid-borne AmpC genes (Nilsson 2015).…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…On livestock units such animals may be used for stock management, pest control, or as companions. AMR bacteria ( E. coli or Salmonella ) have readily been isolated from uncooked pet food or treats (Baede et al., ; Nilsson, ; Pitout et al., ). Furthermore, raw feeding has been identified as a risk factor for the fecal shedding of: multidrug resistant E. coli (Groat, Williams, Pinchbeck, Simpson, & Schmidt, , p. 540), E. coli resistant to extended‐spectrum cephalosporin antimicrobials (Baede et al., ; Groat et al., , p. 540; Lefebvre, Reid‐Smith, Boerlin, & Weese, ), and antimicrobial‐resistant Salmonella (Leonard et al., ).…”
Section: Control and Elimination Of Amr Organismsmentioning
confidence: 99%
“…The foregoing findings may be considered with the high counts of Enterobacteriaceae often encountered in raw foods, plus study evidence of a low incidence of ESBL/AmpC phenotype enteric organisms from heat-treated food (Baede et al 2017). Taken together, this indicates that raw feeding may elevate the risk of the multiplication and dissemination of such antimicrobial resistances.…”
Section: Antimicrobial Resistancementioning
confidence: 94%
“…There is particular concern currently over the spread of extended-spectrum beta-lactamase (ESBL) resistance genes, typically borne on transmissible plasmids, which confer reduced susceptibility to the higher generation cephalosporins that are considered of critical importance in human medicine. Members of Enterobacteriaceae bearing ESBL and/or the related AmpC-type resistance have been found to be prevalent among raw pet foods in studies conducted in the Netherlands, Italy and the Nordic countries (Baede et al 2017;Nilsson 2015;van Bree et al 2018).…”
Section: Antimicrobial Resistancementioning
confidence: 99%
See 1 more Smart Citation